Persepsi Milenial terhadap Gaya Kepemimpinan Calon Presiden Tahun 2024 - Tri Widyastuti; Pramelani Pramelani (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2021)
In Indonesia, presidential elections are held every five years. In 2024, presidential elections will begin again. The president is the leader of a country who can move his people to be able to build his country to be advanced and good in the eyes of the world. The productive population in Asia, including Indonesia, is mostly occupied by millennials. Millennials can contribute to the development of the country. The names of the presidential candidates for 2024 have also been published in the media. Therefore, the authors are interested in examining how millennials perceive the leadership style of Indonesia's presidential candidates in 2024.This research method is qualitative with random sampling of informants. Informants from this study were the millennial group where the researchers conducted interviews in collecting data. This research then produced several findings. Millennials' perception of the leadership style of the Indonesian presidential candidate in 2024 is that the candidate for the country's leader they choose has a populist and democratic leadership style, has good interactive communication skills to the people, is able to motivate especially millennials through social media, has good analytical skills and makes decisions quickly overcome the problems that exist in the community and management skills are also good based on the experience they have. Millennials also give the perception that if their presidential candidate is elected as the leader of the country, the leadership style must be dynamic to keep up with the times.